Designing modern Germany - Aynsley, Jeremy. (Reaktion Books, 2009)
An account of the extraordinarily rich and complex history of German design since 1870. Jeremy Aynsley introduces key figures and offers analyses of their work across a range of media: graphics, interiors, industrial and furniture design, crafts, fashion and architecture.